Kritik Terhadap Pelayanan Publik Pemerintah Daerah di Indonesia - rani wardaniah (Dialektika Publik, 2022)
This study aims to analyze the criticism of local government public services in Indonesia. Complex problems with public services that often occur in services at the local government level. This is because the local government is an extension of the central government to provide rights and obligations in meeting the needs of the community as citizens. This study uses descriptive qualitative research methods to analyze in depth related to criticism of public services in local governments. The data obtained through 25 local and national online news and 25 national journal articles. The results of the analysis of this study indicate that the causes of criticism of public services are; 1) Undeveloped Performance Culture; 2) Incompetent human resources for apparatus, 3) Overlapping tasks, 4) Rule-based or bureaucratic mindset, 5) lack of understanding of standards. This study aims to analyze criticisms of local government public services in Indonesia. Complex problems with public services that often occur in services at the local government level. This is because the local government is an extension of the central government to provide rights and obligations in meeting the needs of the community as citizens. This study uses descriptive qualitative research methods to analyze in depth related to criticism of public services in local governments. The data obtained through 25 local and national online news and 25 national journal articles. The results of the analysis of this study indicate that the causes of criticism of public services are; 1) Undeveloped Performance Culture; 2) incompetent human resources for apparatus, 3) overlapping tasks, 4) rule-based or bureaucratic mindset, 5) low understanding of public service standards.